Effects of plant lectins on in vitro fibroblast proliferation - Sell,Ana Maria (2003)
Lectins are carbohydrate-binding proteins that have been isolated from various sources and presented a wide spectrum of biological activities. The effects of four lectins, namely, Phaseolus vulgaris phytohemagglutinin, PHA, wheat germ agglutinin, WGA, Artocarpus integrifolia seed lectins, jacalin and artocarpin, on in vitro fibroblasts proliferation were investigated. The lectins did not influence the initial cell adhesion to the plate. PHA and WGA at 10-20 µg/mL concentrations significantly decreased fibroblasts proliferation. At these concentrations, they caused morphological alterations on cells and over 80 µg/mL, promoted cell death. Neither jacalin nor artocarpin significantly affected cell proliferation.